Myanmar : time for new regional diplomacy - Cook, Alistair David Blair (2021)
As the confrontation between the protestors and the military in Myanmar continues to deteriorate, now more than ever is the time for regional diplomacy. Countries in the region can be the bridge needed to the people in Myanmar and the wider international community.